A suggested computer-based model for using Nasreddin Hodja’s anecdotes in preschool education - Kabadayı, Abdulkadir (Journal of Human Sciences, 2006)
Researchers have been manipulating the technology in education as well as in other fields and investigating the most effective ways of using it in the classroom. Therefore, they try to present any material which has an affect on the learners’ development, by integrating technological devices in the classroom atmosphere. Being aware of the fact that 70 percent of the children’s mental, language and cognitive domains have developed during preschool education, pedagogues are quite sensitive to preschool education and are in search for taking necessary precautions to enable them cognitive, psycho-motor and affective domains in the community. It is clear that preschool children are quite interested in the cartoons and motivated to perceive the world via cartoons on TV. Taking the point into consideration, in this article, a technology-based model is suggested by explaining the methods and techniques of use of the Nasreddin Hodja’s anecdotes as educational equipments in virtual atmosphere. In this model, it is explained how the Nasreddin Hodja’s anecdotes will develop students’ cognitive, affective and psycho-motor domains effectively displaying grade by grade illustration.